Exploring natural microbial resources for the discovery of anti-malarial compounds. (December 2021) - Waluyo, Danang; Prabandari, Erwahyuni Endang; Pramisandi, Amila; Hidayati, Dyah Noor; Chrisnayanti, Evita; Puspitasari, Dian Japany; Dewi, Diana; Suryani,; Kristiningrum,; Oktaviani, Avi Nurul; Afrianti, Kiki Rizkia; Nonaka, Kenichi; et al.
Abstract: Microorganisms in nature are highly diverse biological resources, which can be explored for drug discovery. Some countries including Brazil, Columbia, Indonesia, China, and Mexico, which are blessed with geographical uniqueness with diverse climates and display remarkable megabiodiversity, potentially provide microorganismal resources for such exploitation. In this review, as an example of drug discovery campaigns against tropical parasitic diseases utilizing microorganisms from such a megabiodiversity country, we summarize our past and on-going activities toward discovery of new antimalarials. The program was held in a bilateral collaboration between multiple Indonesian and Japanese research groups. In order to develop a new platform of drug discovery utilizing Indonesian bioresources under an international collaborative scheme, we aimed at: 1) establishment of an Indonesian microbial depository, 2) development of robust enzyme-based and cell-based screening systems, and 3) technology transfer necessary for screening, purification, and identification of antimalarial compounds from microbial culture broths. We collected, characterized, and deposited Indonesian microbes. We morphologically and genetically characterized fungi and actinomycetes strains isolated from 5 different locations representing 3 Indonesian geographical areas, and validated genetic diversity of microbes. Enzyme-based screening was developed against two validated mitochondrial enzymes from Plasmodium falciparum, dihydroorotate dehydrogenase and malate:quinone oxidoreductase, while cell-based proliferation assay was developed using the erythrocytic stage parasite of 3D7 strain. More than 17 thousands microbial culture extracts were subjected to the enzyme- and cell-based screening. Representative anti-malarial compounds discovered in this campaign are discussed, including a few isolated compounds that have been identified for the first time as anti-malarial compounds. Our antimalarial discovery campaign validated the Indonesian microbial library as a powerful resource for drug discovery. We also discuss critical needs for selection criteria for hits at each stage of screening and hit deconvolution such as preliminary extraction test for the initial profiling of the active compounds and dereplication techniques to minimize repetitive discovery of known compounds.